Association of the new zero‑tolerance drinking and driving law with hospitalization rate due to road trafc injuries in Brazil - Souza, Cássia Rebeca de Lima (2022)
We investigated the association of the new zero-tolerance drinking and driving law (Law 12,760, Dec. 2012) with hospital admissions due to road trafc injuries in Brazil by using interrupted time series from 2008 to 2019. We used linear regression designed to adjust for autocorrelation and Cumby–Huizinga test for residual autocorrelation. Newey–West standard errors was used to handle heteroscedasticity. We used ICD-10 codes for land transport accidents (V01–V89). The hospitalization rate was calculated per 100,000 inhabitants. The sources were the Hospital Information System and the Brazilian Institute for Geography and Statistics. Pre- and postintervention consist of 59 and 85 months, respectively. For Brazil, the hospitalization rate was associated with a reduction of 0.34 (p = 0.097; 95% CI − 0.74 to 0.06) in the frst month of the intervention (Dec. 2012), followed by a signifcant change in the hospitalization trend. Compared to the period prior to the intervention, the monthly trend was associated with a reduction of 0.05 (p < 0.01; 95% CI − 0.06 to − 0.04) in the post period. These results stand in agreement with subgroup analyses for the Brazilian regions, although North and Northeast regions did not immediately reduce hospitalization rates (level change). Our results suggested that 440,599 hospitalizations for land transport accidents would be averted by the new zero-tolerance drinking and driving law from Dec. 2012 to Dec. 2019 in Brazil. Even using a quasiexperimental approach, our fndings must be interpreted with caution due to observational design and registration faws surrounding our data.